Wrongful Birth With Special Regard to Hungary - Julesz, Máté (Medicine, Law & Society, 2025)
Even though wrongful pregnancy and wrongful life claims are rejected by Hungarian courts, a wrongful birth action is permitted. According to the Curia’s uniformity decision 2/2022, damages for wrongful birth are reduced to the costs of raising a disabled child minus the possible costs of rearing a healthy one. The disability rights critique is very strong from the US to the EU. Nevertheless, a violation of the parents’ personal right to family planning requires compensation in the EU and in numerous US states. A wrongful birth claim does not discount the disabled child’s human dignity.